PELABELAN PERAN SEMANTIS MENGGUNAKAN TATA BAHASA KASUS - Indrawati, Nur; Bijaksana, M Arif; Agustin, Ririn Dwi (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2013)
The Application of semantic role labeling as one of the tasks from natural language processing include a variety of fields, such as machine translation, text summarization, and text mining. Semantic roles labeling is used in other text mining as the preprocessing of the concept-based mining system, which utilizes graphical representation and statistical-based data to find the concept of a sentence in the document text. Searching the concept on the preprocessing of text mining are one of the way to get valuable information from the sentence, taking into account the semantic of every word in a sentence. The results of Semantic role labeling in this paper solves a problem for labeling a single sentence semantic roles in Indonesian language, using computerized-based.